Strategi Pembelajaran Kolaboratif dalam Maharah Kitabah di MA Asy-Syifa Totikum - Miftahul Fadliah Buhun; Anisah Nasution; Muassomah (Universitas Yudharta Pasuruan, 2021)
This study aims to determine the effect of collaborative learning strategies on writing skill with a face to face learning process at MA Asy-Syifa Totikum. This study uses descriptive qualitative methods with three data collection techniques, namely: observation, interviews, and documentation. The results of this study indicate with the implementation of collaborative strategies in learning writing skill, student learning outcomes have increased. As for the application of collaborative strategies in learning Arabic writing skill, it is carried out through the following stages: determining learning objectives, dividing students into heterogeneous groups based on the results of the Arabic language report scores and gender, the teacher gives free writing assignments to all students, students are asked to choose a predetermined theme then students write based on that theme using vocabulary, tarkib, and language skill that have been learned, if they have difficulty in making essays students discuss with their group friends. In addition, students are asked to write new vocabularies under the essay, so that students can learn, add vocabulary, and improve students memory.